Formation of research skills of younger students in the learning process «World cognition» - Койшебаева, Зарина; Жусупбекова, Гульсара (Pedagogy and Psychology, 2020)
This article is devoted to the formation of research skills and abilities of younger students in the process of teaching the subject «Knowledge of the world». The research is based on the ideas and views of foreign and domestic scientists. The essence of the concepts «research activity» and «research skills»is defined. The main emphasis is based on the features and specifics of the development of research skills of primary school students. The authors consider the research skills of primary school children through the prism of interrelated conceptual categories: «research», «skills and abilities», «research activity». Describes some aspects of the organization of the educational process and indicates the need for pedagogical influence on the process and content of research activities, which determines the formation of younger students research skills. The authors propose a technological map of an optional lesson on the formation of research skills and abilities for primary school students.